THE COEFFICIENT OF FRICȚION IN THE FRETTING PHENOMENON - Stefan GHIMIŞI (Fiabilitate şi Durabilitate)
Fretting is now fully identified as a small amplitude oscillatory motion which induces a harmonic tangential force between two surfaces in contact. The present paper argues that adhesion forces and elastic deformation in the contact zone may contribute significantly to the relative displacement during fretting of metals A tangential force whose magnitude is less equal on greater than the force of limiting friction will not give rise to a sliding motion. It is determined the energy loss dissipated per fretting cycle